Family Structure and Academic Performance: A Correlational Study Among Junior High School Students (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Family structure plays a vital role in shaping the social, emotional, and academic development of students. This study examined its impact on the academic performance and perceptions of Junior High School students at Silanga National High School, Schools Division of Catbalogan City, during the School Year 2025–2026, using a descriptive-correlational design. Findings revealed that among the profile variables, only sex and parents’ occupation showed significant relationships with family structure. Parents’ occupation demonstrated a moderate association, while sex showed a minimal relationship. The null hypothesis regarding the relationship between family structure and students’ perceptions of parental roles, decision-making, emotional support, discipline, and family unity was rejected, indicating that students from non-intact families perceived these aspects slightly less positively; however, economic support showed no significant relationship. Conversely, the null hypothesis on academic performance was accepted, suggesting minimal to no impact of family structure. Most students came from intact families and achieved satisfactory to very good academic performance, although many experienced limited time with parents. Recommendations include strengthening parental engagement, implementing gender-sensitive programs, enhancing emotional support, providing academic interventions, offering targeted counseling, fostering school-community collaboration, and establishing recognition programs. Future research may explore additional variables, longitudinal designs, and qualitative approaches.